The effect of n-3 fatty acids on glucose homeostasis and insulin sensitivity - Flachs, P; Rossmeisl, M; Kopecky, J (Physiological research, 2014)
Type 2 diabetes (T2D) as well as cardiovascular disease (CVD) represent major complications of obesity and associated metabolic disorders (metabolic syndrome). This review focuses on the effects of long-chain n-3 polyunsaturated fatty acids (omega-3) on insulin sensitivity and glucose homeostasis, which are improved by omega-3 in many animal models of metabolic syndrome, but remain frequently unaffected in humans. Here we focus on: (i) mechanistic aspects of omega-3 action, reflecting also our experiments in dietary obese mice; and (ii) recent studies analysing omega-3's effects in various categories of human subjects. Most animal experiments document beneficial effects of omega-3 on insulin sensitivity and glucose metabolism even under conditions of established obesity and insulin resistance. Besides positive results obtained in both cross-sectional and prospective cohort studies on healthy human populations, also some intervention studies in prediabetic subjects document amelioration of impaired glucose homeostasis by omega-3. However, the use of omega-3 to reduce a risk of new-onset diabetes in prediabetic subjects still remains to be further characterized. The results of a majority of clinical trials performed in T2D patients suggest that omega-3 have none or marginal effects on metabolic control, while effectively reducing hypertriglyceridemia in these patients. Despite most of the recent randomized clinical trials do not support the role of omega-3 in secondary prevention of CVD, this issue remains still controversial. Combined interventions using omega-3 and antidiabetic or hypolipidemic drugs should be further explored and considered for treatment of patients with T2D and other diseases.
Keywords: Animals; homeostáza; Fatty Acids, Omega-3; výsledek terapie; Diabetes Mellitus, Type 2; lidé; Blood Glucose; Mice; Homeostasis; diabetes mellitus 2. typu; Insulin; Treatment Outcome; myši; omega-3 mastné kyseliny; medicína založená na důkazech; Insulin Resistance; inzulinová rezistence; zvířata; inzulin; krevní glukóza; Evidence-Based Medicine; Humans